If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(8 + -1x) = 3 + -1(x + -6) 5 + (8 * -1 + -1x * -1) = 3 + -1(x + -6) 5 + (-8 + 1x) = 3 + -1(x + -6) Combine like terms: 5 + -8 = -3 -3 + 1x = 3 + -1(x + -6) Reorder the terms: -3 + 1x = 3 + -1(-6 + x) -3 + 1x = 3 + (-6 * -1 + x * -1) -3 + 1x = 3 + (6 + -1x) Combine like terms: 3 + 6 = 9 -3 + 1x = 9 + -1x Solving -3 + 1x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 1x + x = 9 + -1x + x Combine like terms: 1x + x = 2x -3 + 2x = 9 + -1x + x Combine like terms: -1x + x = 0 -3 + 2x = 9 + 0 -3 + 2x = 9 Add '3' to each side of the equation. -3 + 3 + 2x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 9 + 3 2x = 9 + 3 Combine like terms: 9 + 3 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= | | 40=5w-15 |